Productivity shocks and the New Keynesian Phillips Curve: Evidence from US and Euro area - Gene Ambrocio; Tae-Seok Jang (Kiel Institute for the World Economy (IfW), 2009)
This paper seeks to understand dynamics of inflation and marginal cost (labor share) in models that account for the inclusion of productivity shocks in standard New Keynesian Phillips Curve (NKPC). The question of interest is on the empirical importance of and whether productivity shocks shift the Phillips curve using U.S. and Euro area data. Highlighting the inclusion of productivity growth, we employ a hybrid model specification augmented with a productivity term. The model is estimated using the Generalized Method of Moments (GMM) following Gali and Gertler (1999). Our main finding is that a simple extension of the baseline and hybrid models using more recent data (2006:Q4 for the US and 2005:Q4 for the Euro area) yield less convincing results than the previous literature. Furthermore, our estimation results provide some support for the inclusion of productivity growth particularly for the US. We conclude that a better understanding of the inflation-unemployment tradeoff requires accounting for shifts in the Phillips Curve due to productivity shocks.
Keywords: E24; E31; J3; 330; New Keynesian; Phillips Curve; Productivity Growth; GMM; New-Keynesian Phillips Curve; Produktivität; Schock; Momentenmethode; Schätzung; USA; EU-Staaten